Prevalence and Relatedness of mcr-1-Mediated Colistin-Resistant Escherichia coli Isolated From Livestock and Farmers in Japan - Nakano, Akiyo; Nakano, Ryuichi; Nishisouzu, Ryuji; Suzuki, Yuki; Horiuchi, Saori; Kikuchi-Ueda, Takane; Ubagai, Tsuneyuki; Ono, Yasuo; Yano, Hisakazu (Frontiers in Microbiology, 2021)
Colistin is used to treat infectious diseases in humans and livestock; it has also been used as a feed additive for livestock for approximately 50 years. Since the mcr-1 plasmid-mediated colistin resistance gene was discovered in China in 2015, it has been detected worldwide, mainly in livestock. In this study, we investigated the prevalence and characteristics of mcr-mediated colistin-resistant Escherichia coli in livestock and farmers in Japan. We collected fecal samples from 295 healthy livestock (202 cattle and 93 swine) and 62 healthy farmers from 72 livestock farms (58 cattle farms and 14 swine farms) between 2013 and 2015. Twenty-eight mcr-1-harboring E. coli strains were isolated from 25 livestock (6 cattle and 19 swine) and three farmers (2 cattle farmers and one swine farmer). The prevalence rates of mcr-1-harboring E. coli in livestock and farmers were 8.47% and 4.84%, respectively. Of the 28 strains, the resistance genes of three were transferable via the mcr-1-coding plasmids to E. coli J53 at low frequencies (10-7–10-8). Six strains coharbored mcr-1 with CTX-M β-lactamases (CTX-M-14, CTX-M-27, or CTX-M-156). Of the isolates obtained from livestock and farmers in four farms (farms C, I, N, and P), nine strains had the same genotypical characteristics (sequence types and pulsed-field gel electrophoresis band patterns), plasmid characteristics (incompatibility group and plasmid transferability), and minimum inhibitory concentrations. Thus, the findings suggested that clonal strains could spread among livestock and farmers within farms. To our knowledge, this is the first study to detect clonal relatedness of mcr-1-mediated colistin-resistant E. coli in livestock and farmers. It is suggested that farmers are at a higher risk of acquiring mcr-1-harboring strains, calling for our attention based on the One Health concept.